Estimation-based joint position sense: comparing self-rated and measured accuracy across sexes - Wootaek Lim (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: The validity of self-rated joint position sense (JPS) remains inconclusive. Moreover, previous experimental designs for JPS assessment often failed to reflect real-life movement execution, and studies addressing sex differences in JPS are limited. Therefore, this study aimed to investigate the relationship between perceived JPS (self-rated JPS) and actual joint position error (JPE), and examine sex-based differences in JPE. Methods: Thirty-three apparently healthy adults participated in the study and performed an elbow flexion to 90°, relying on proprioceptive inference rather than memorized reproduction. Ordinal logistic regression was used to analyze the relationship between the perceived JPS and JPE. JPS acuity was evaluated using constant error and absolute error (AE), while the reliability of repeated measures was assessed using the intraclass correlation coefficient (ICC). Results: Ordinal logistic regression revealed that higher JPE values are associated with lower self-ratings of JPS ability. In the analysis of sex differences, females exhibited significantly greater AEs than did males, indicating lower proprioceptive accuracy. However, ICC values showed slightly higher reliability in females, suggesting more consistent performance across repeated trials despite larger deviations from the target angle. Conclusion: This study provides new evidence on the relationship between self-perceived and measured JPS, as well as sex-related differences in proprioceptive performance. The findings underscore the importance of considering sex and individual self-awareness in proprioceptive training strategies. Therefore, incorporating cognitive feedback may enhance JPS self-perception and improve training outcomes in clinical and sporting contexts.